PENYULUHAN PEMANFAATAN BUAH BIT TERHADAP PENINGKATAN HEMOGLOBIN PADA IBU HAMIL DENGAN ANEMIA - Septa Dwi Insani; Kristin Natalia; Tedty Rohaya Tinambunan; Naimah Nasution; Novalita Ira Aprina Gultom (INSTITUT KESEHATAN DELI HUSADA, 2023)
Beet root or its foreign language Beta Vulgaris. L is a root-shaped plant that looks like a tuber that belongs to the Amaranthacae family. One of the non-pharmacological therapies that has great health benefits, one of which is the high content of folic acid and iron is beets. Pregnancy is usually associated with several unwanted health hazards, including anemia. Every year, around half a million women suffer from poor health, disability or death from complications related to pregnancy and childbirth. This community service aims to invite mothers to increase the hemoglobin of anemic pregnant women by consuming beets. The implementation of this activity was carried out for pregnant women by providing information and education about anemia, the benefits of beets and how to consume them so that they can be a drink that can increase hemoglobin levels of pregnant women. Furthermore, pregnant women measured their level of knowledge by being given a Pre-Test and Post-Test and the result was that 77% of 20 pregnant women better understood the benefits of beetroot which is a non-pharmacological therapy to prevent anemia.